2006
DOI: 10.1148/radiol.2413051896
|View full text |Cite
|
Sign up to set email alerts
|

Perforated versus Nonperforated Acute Appendicitis: Accuracy of Multidetector CT Detection

Abstract: Although certain multidetector CT findings are very specific for the diagnosis of perforated appendicitis, overall multidetector CT sensitivity is poor. Unless abscess or extraluminal gas is present, multidetector CT cannot enable the diagnosis of perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(71 citation statements)
references
References 21 publications
6
63
1
1
Order By: Relevance
“…Others have suggested that overall CT sensitivity for this task may be poor since unless abscess or extraluminal gas is present, CT cannot enable the diagnosis of perforation (25). On the other hand, taking into account acute appendicitis as a whole, with concern to all of its pathological stages, accurate diagnosis seems to be affected by the exploitation of imaging modalities.…”
Section: Age Did Not Significantly Differ Between Groups (Anova P-vamentioning
confidence: 99%
“…Others have suggested that overall CT sensitivity for this task may be poor since unless abscess or extraluminal gas is present, CT cannot enable the diagnosis of perforation (25). On the other hand, taking into account acute appendicitis as a whole, with concern to all of its pathological stages, accurate diagnosis seems to be affected by the exploitation of imaging modalities.…”
Section: Age Did Not Significantly Differ Between Groups (Anova P-vamentioning
confidence: 99%
“…[6] Computed tomography is a highly reliable non-invasive diagnostic tool to assess for acute appendicitis. Abdominal CT is a well-established technique in the study of acute abdominal pain and has shown high sensitivity and specificity for diagnosing and differentiating appendicitis, providing an accurate diagnosis in the early stages of the disease [7], [8]. Barium studies may be used to demonstrate abnormally located caecum and ascending colon.…”
Section: Discussion:-mentioning
confidence: 99%
“…3,8,[10][11][12][13]15,16 For example, Hansen et al described radiologic factors that strongly correlate with the histologic diagnosis of AA, as follows: (i) the appendix diameter, (ii) periappendiceal fat staining, (iii) appendicoliths, (iv) extraluminal air, (v) dependent fluid.…”
Section: Discussionmentioning
confidence: 99%